1987
DOI: 10.1295/polymj.19.839
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study of Oxygen Sorption and Diffusion in a Membrane Containing a Cobalt Porphyrin Complex

Abstract: ABSTRACT:The kinetics and equilibrium of molecular oxygen sorption in the membrane contammg [cx,cx',cx'',cx'''-meso-tetrakis(o-pivalamidophenyl)porphinato]cobalt(II)-1-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Nishide et al and other authors have reported that the cobaltprophyrin (CoP) membrane is effective for oxygen facilitated transport. The carrier of the metal complex is effective for specific gas species transport and the membranes show high permeability (Shinohara et al, 2005;Shentu and Nishide, 2003;Nishide et al, 1986) and permselectivity (Nishide et al, 1987;Shoji et al, 2008;Chikushi et al, 2014). Cobalt tetraphenylporphyrin (CoTPP) consists on one side of a porphyrin plane ; the other side reacts with imidazole ligand to improve the oxygen binding affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Nishide et al and other authors have reported that the cobaltprophyrin (CoP) membrane is effective for oxygen facilitated transport. The carrier of the metal complex is effective for specific gas species transport and the membranes show high permeability (Shinohara et al, 2005;Shentu and Nishide, 2003;Nishide et al, 1986) and permselectivity (Nishide et al, 1987;Shoji et al, 2008;Chikushi et al, 2014). Cobalt tetraphenylporphyrin (CoTPP) consists on one side of a porphyrin plane ; the other side reacts with imidazole ligand to improve the oxygen binding affinity.…”
Section: Introductionmentioning
confidence: 99%
“…CoP is also characterized by a deep red color, and the oxygen-adduct formation is accompanied by a sharp deoxy-oxy spectral change with isosbestic points. 35 H.N. has reported that a polymer layer composed of CoP ligated with polyvinylimidazole or polyvinylpyridine serves as a colorimetric oxygen sensor due to its visible absorption spectral change.…”
Section: Introductionmentioning
confidence: 99%
“…The CoP membranes are also characterized by a deep red color, and the oxygen-adduct formation is accompanied by a sharp deoxy-oxy spectral change with isosbestic points. 9 Pretsch et al and the authors have reported 10 in a collaboration that the membranes composed of the CoP-poly(octyl methacrylate-co-1-vinylimidazole) complexes serve as a new type of oxygen-sensitive components for optical sensors. In this paper, the authors have succeeded in preparing CoP membranes composed of three different polymer-ligands (Chart 1) by taking into account the ligating equilibrium constants: The useful oxygen-response range was significantly extended, and the operational lifetime was extremely prolonged for the prepared CoP membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The CoP acts as a fixed carrier of oxygen and facilitates the transport of oxygen in the membrane to display oxygen permselectivity. The CoP membranes are also characterized by a deep red color, and the oxygen-adduct formation is accompanied by a sharp deoxy−oxy spectral change with isosbestic points in a collaboration that the membranes composed of the CoP−poly(octyl methacrylate- co -1-vinylimidazole) complexes serve as a new type of oxygen-sensitive components for optical sensors.…”
Section: Introductionmentioning
confidence: 99%